Transmit beampattern design for airborne phased‐MIMO radar. Issue 20 (22nd August 2019) - Dong, Ye; Cheng, Fengfeng; Cao, Lanying
Abstract : Airborne phased‐MIMO radar based on sub‐arrays is investigated that can combine the advantages of both MIMO radar and phased array radar. The transmit beampattern design method for airborne phased‐MIMO radar is proposed that can control the transmit beam width to raise the airspace coverage by transmitted signals design. In order to avoid grating lobes and achieve low sidelobes, the irregular sub‐array partition is also proposed. Simulation results show that the transmit beampattern of airborne phased‐MIMO radar based on irregular sub‐arrays has wider beamwidth and lower sidelobes that can improve stability of detecting and tracking hypervelocity moving targets in the air. Simulation results also validate the effectiveness of the transmit beampatern design for phased‐MIMO radar with irregular sub‐arrays.